STRENGTH TRAINING ANATOMY - Delavier, Frederic (Human Kinetics, 2001)
New exercises and stretches for each of the major muscle groups--to give readers an understanding of how muscles perform while training, in a resource that combines the detail of top anatomy texts with the best of strength training advice.